TOHIR MALIKNING “ALVIDO BOLALIK” QISSASIDA QOʻLLANGAN SOTSIOLEKTLARNING SINTAKTIK KONSTRUKSIYALARI VA MA’NOVIY JIHATLARI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses Tahir Malik's “Alvido Bolalik” and the sociolects, or slang, utilized in it. It also discusses the manners employed in the creative work's speech acts.
Keywords: speech act, slang, slang, speech etiquette, language socialization, language construction.